2012
DOI: 10.1007/s00421-012-2479-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating hormone and cytokine response to low-load resistance training with blood flow restriction in older men

Abstract: It has been suggested that circulating hormones and cytokines are important in the adaptive response to low-load resistance training (LLRT) with blood flow restriction (BFR); however, their response following this type of training in older men is unclear. Seven healthy older men (age 71.0 ± 6.5 year, height 1.77 ± 0.05 m, body mass 80.0 ± 7.5 kg; mean ± SD) performed five sets of unilateral LLRT knee extensions (20 % 1-RM) of both limbs, with or without BFR in a counterbalanced order. For the BFR condition, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 54 publications
3
71
0
2
Order By: Relevance
“…However, while serum IGF-1 increased immediately following resistance exercise in both hypoxia and normoxia, there were no significant differences between conditions [15]. This is in agreement with previous BFR research, where GH response is typically augmented following resistance exercise with BFR, while the IGF-1 response appears equivocal [51,55]. Similarly, whilst serum testosterone levels were significantly increased following resistance exercise in both hypoxia and normoxia, no significant differences were found between conditions [15,16].…”
Section: Hormonal Responsessupporting
confidence: 88%
See 2 more Smart Citations
“…However, while serum IGF-1 increased immediately following resistance exercise in both hypoxia and normoxia, there were no significant differences between conditions [15]. This is in agreement with previous BFR research, where GH response is typically augmented following resistance exercise with BFR, while the IGF-1 response appears equivocal [51,55]. Similarly, whilst serum testosterone levels were significantly increased following resistance exercise in both hypoxia and normoxia, no significant differences were found between conditions [15,16].…”
Section: Hormonal Responsessupporting
confidence: 88%
“…However, despite noting enhanced GH responses following low-intensity (20% 1RM) resistance exercise with BFR, neither Fujita et al [51] or Patterson et al [55] observed concomitant increases in IGF-1. This discrepancy may be explained by the different time course of change in GH and IGF-1 [57], with peaks in IGF-1 typically occurring at 16-28 hours following GH release [57,61].…”
Section: Hormonal Responsesmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that metabolic stress induced by low-intensity plus BFRT increases GH secretion and muscle hypertrophy[64,65,78], furthermore, this could stimulate metabolic stress markers, such as IL-6[79,80]. The recovery process is initiated by IL-6 by modulating muscle regulatory genes ( i.e ., MyoD)[81-83] and activating muscle satellite cells[80], and therefore may play a role in regulating muscle growth/hypertrophy[80].…”
Section: Low-intensity Resistance Training Plus Blood Flow Restrictionmentioning
confidence: 99%
“…Therefore, it has become an enigma as to why these effects are observed despite the low-intensity nature of BFR exercise not typically associated with gains in muscle mass. More recent studies have focused on the cellular events that underlie the mechanisms responsible for muscle hypertrophy as a result of BFR exercise, including myogenic and proteolytic markers (25), correlational evidence of cell signaling pathways (17,18,20,26), rates of muscle protein synthesis (17,18,20), hormonal responses (17,18,29), and satellite cell activation (27,35). However, despite this recent research focus, a clear mechanistic explanation for how BFR exercise increases muscle cell size is unknown.…”
mentioning
confidence: 99%